Sleep disturbance scale for children as a diagnostic tool for sleep disorders in adolescents - Herwanto Herwanto; Hesti Lestari; Sarah M. Warouw; Praevilia M. Salendu (Indonesian Pediatric Society, 2018)
Background. Sleep is an essential needs for every children. Sleep may cause a large effect on mental health, emotional, physical and immune system. If sleeping time is not sufficient, then sleep disturbance may occur. Objective assessment of the sleeping quality can be done by using Polysomnography and Actigraphy, while for assessing the subjectivity of sleeping quality and quantity can be used questionnaires or interviews. Sleep Disturbance Scale for Children or SDSC is a multidimensional sleeping assessment questionnaire. Objective. To determine the quality of sleeping in adolescents using SDSC. Methods. We conducted a diagnostic test study using cross sectional method, during March to April 2015 at the elementary schools in manado. The inclusion criteria were healthy adolescent aged 10 to 12 years, the parents were willing to sign the informed consent and answer the questionnaire, agreed to attach the wristactigraph. All datas were analyzed using chi square test and table 2 x 2 to showed sensitivity, specificity, positive predicitive value and negative predictive value. Results. Of 60 adolescents, 31 were female and 29 were male with the mean age 11.39 years. The results showed the sensitivity of SDSC was 80.6%, the specificity was 37.9%, the positive predictive value was 58.1% and negative predictive value was 64.7%. Conclusions. Sleep Disturbance Scale for Children is a good screening tool for early detection of sleep disorders in a adolescent.